ETIKA APARAT PEMERINTAH TERHADAP EFEKTIVITAS PROGRAM PENANGANAN COVID-19 DI KELURAHAN RAPPANG KECAMATAN PANCA RIJANG KABUPATEN SIDENRENG RAPPANG - Muhammad Fitrah; Monalisa Ibrahim; Sapri Sapri (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
This study aims to determine the ethics of royal employees regarding the effectiveness of the Covid-19 control program. The population in this study is as many as 3,745 people in the village of Rappang, where the sample used is Probability Sampling with the Easy Rawak Sampling technique using the Slovin formula with a total sample of 97. The data collection techniques used are observation, inquires, bragging, and studies. Libraries and Documentation. The data analysis technique used is descriptive statistics, hypothesis testing using SPSS 16.0 and Likers Scale. The results of this study show that the ethics of royal employees regarding the effectiveness of the Covid-19 control program is 55.1% in the poor category. Factors that affect the effectiveness of the covid-19 control program are 59.5% with the